The Trial of Robert Barker: A Story of Witchcraft and the Occult in Upper Canada - Fehr, R. (Ontario History)

(untitled) (The Ontario Historical Society, 2025)
Fact or fiction, the Baldoon Mystery is the folkloric foundation of Wallaceburg, a small town in Southwestern Ontario. Stories of a witch’s curse and a witch doctor’s prescription during the mysterious events of 1829 and 1830 underpin the supernatural tale. There is a space between material veracity and folklore; somewhere in between stands the little-known headmaster of the local schoolhouse. Spectacular attempts to summon God and the use of magic on behalf of the community came at a cost, however, as accusations of blasphemy and fraud collided with accusations of witchcraft. The story of Robert Barker has long been obscured in the shadow of the extraordinary accounts told of Baldoon’s early days. Yet, Barker’s ordeal opens further exploration into the role of gossip and accusations during times of social tension.